Disulfidptosis-related lncRNA signature to assess the immune microenvironment and drug sensitivity in acute myeloid leukemia - Yuying Zhao; Hai-en Cheng; Jingfei Wang; Yunke Zang; Zhijun Liu; Yanhua Sun; Yanli Sun (Scientific Reports)
Abstract Acute myeloid leukemia (AML) represents a hematological malignancy that arises from the abnormal proliferation of progenitor cells or myeloid hematopoietic stem. The current standard treatments for AML include chemotherapy and hematopoietic stem cell transplantation. However, chemotherapy suffers from high toxicity and a shortage of hematopoietic stem cell donors, which significantly shortens patient survival. A new type of cell death, disulfidptosis, has shown potential in medicine. However, its specific biological mechanism of action in AML is currently unclear. This research developed a prognostic model of disulfidptosis-related long non-coding RNAs (DRLs) based on 132 AML patients with GDC TCGA Acute myeloid leukemia (LAML). In this model, eight DRLs: AL049835.1, EXOC3-AS1, AC009237.14, LINC00944, AP002761.4, LINC00926, AC010247.2, and AC099811.5 were included. Patients with high-risk AML evaluated based on the model had shorter survival, significant infiltration of monocytes and M2 macrophages, and elevated transcriptional levels of immune checkpoint genes. In addition, AML was classified into three subtypes according to the model, and patients in different subtypes showed different overall survival (OS) and drug sensitivity. Overall, we formulated a pioneering prognostic model utilizing DRLs, achieving precise AML outcome predictions. The correlations between the DRL prognostic models and the AML immune microenvironment, drug sensitivity, and tumor subtype were explored. In addition, further studies on the molecular mechanisms of key biomarkers, such as LINC00944 and LINC00926, will greatly contribute to our understanding of AML pathogenesis and drug resistance mechanisms in the future.